The participation process to revive the No-nay Folk Song of Nong-Sala community, Cha-am district, Petchburi province - พุฒจร, ทิพย์สุดา; เวชพงศ์, ฐิติมา; พรหมนิมิตรกุล, เกศราพร; วชิรสิโรดม, อรรถพล (Journal of Liberal Arts Prince of Songkla University, 2016)
The objective of this research was to study a revival of No-nay folk songs with participation process of Nong-Sala community, Cha-am, Petchburi. The participatory action research methodology was used with the participation of teachers from Nong-Sala School, members of Nong-Sala district administration, and Poh-Pleng and Mae-Pleng from Nong-Sala community. The researchers and participants were working together in every process including planning, implementation, evaluation, and improvement. The results showed that the No-nay song was called Songkarn song because people sang this song during Songkarn Festival. A period of time after that, the name of the song was called following its first word and then was changed to No-nay instead. No-nay was sung as a group during spared time after farming. It is a fun and exciting activity that allows young people to court each other. The No-nay songs are of two types: No-nay and Loy songs. The number of words and internal and external rhymes are not fixed. They depend on singers’ capabilities and skills in language usage. The last word of the line always rhymes with the last word of the next line called Hua-Deiw Poem. The No-nay song has no clear pattern. Thus, there is no qualification of singers and their costume. The song requires a lot of singers; lead-song (Pleng Nam) singers and follow-song (Pleng Rub) singers, along with clappers clapping their hands to give a rhythm. The lead-song is sung rotatedly and then other singers sing the follow-song and dance in pairs. The lyrics of the No-nay songs exhibit continuity of the content. Most of them came from the old songs and some of them were new composed. Some of the lyrics are about sugar palm planters’ life, which was the traditional way of life of the community.